Rail Transport Service Performance through Analytical Hierarchy Approach and Data Envelopment Analysis for PT. Kereta Api Indonesia (KAI) - Parwadi Moengin; Fani Puspitasari; Nilla Nilla (JURNAL TEKNIK INDUSTRI, 2020)
Abstract--Railway transport being a service is provided in a space and time dimension. Providing a better quality of service requires higher inputs, so evaluating the performance without these considerations would give a biased result. The purpose of this paper is to assess the performance of the rail transport service by including the service delivery perspective of railways and look at the holistic concept of service delivery. The quality of service parameters have been chosen within the constraints imposed by availability of data and the formulated data envelopment analysis (DEA). The quality of service parameters include: punctuality; the level of consequential train accidents (safety); and the level of public complaints (customer satisfaction). It evaluates the performance of 9 zones of KAI on the basis of their efficiencies and identifies the exemplar zones. The results deduced from these studies can serve as performance targets in reward systems, performance scorecards, and control systems.DEA has been used as a benchmarking tool to evaluate the relative efficiency of the 9 zones. The input parameters are working expenses, number of employees, and equated track kilometers and the output parameters are loading of revenue, punctuality, passenger traffic kilometers, consequential train accidents, and public complaints. Malmquist index has been used to determine the temporal performance of each zone. KAI can use DEA to assess the performance of various zones and for improvement monitoring in the context of being a transport service provider. Inefficient zones can identify the parameters for improvement across the zones and along the time dimension. A huge working force for all the inefficient zones indicate over deployment of resources, which can be seen at the policy level. A redundancy for equated track kilometers indicates a non-optimum use of resources. Not giving enough importance to service quality could be one of the major findings of the inefficient zones.Intisari--Transportasi kereta api sebagai layanan disediakan dalam dimensi ruang dan waktu. Memberikan kualitas layanan yang lebih baik membutuhkan input yang lebih tinggi, sehingga mengevaluasi kinerja tanpa pertimbangan ini akan memberikan hasil yang bias. Tujuan dari makalah ini adalah untuk menilai kinerja layanan transportasi kereta api dengan memasukkan perspektif pemberian layanan kereta api dan melihat konsep holistik pemberian layanan. Parameter kualitas layanan telah dipilih dalam batasan yang diberlakukan dengan mempertimbangkan ketersediaan data dan analisis amplop data yang dirumuskan (DEA). Parameter kualitas layanan meliputi: ketepatan waktu; tingkat konsekuensi kecelakaan kereta api (keselamatan); dan tingkat keluhan publik (kepuasan pelanggan). Makalah ini mengevaluasi kinerja 9 zona (Daerah Operasi) KAI berdasarkan efisiensi mereka dan mengidentifikasi zona contoh. Hasil yang disimpulkan dari penelitian ini dapat berfungsi sebagai target kinerja dalam sistem penghargaan, penilaian kinerja, dan sistem kontrol.DEA digunakan sebagai alat benchmarking untuk mengevaluasi efisiensi relatif dari 9 zona. Parameter input adalah biaya kerja, jumlah karyawan, dan kilometer track yang disamakan dan parameter outputnya adalah pendapatan, ketepatan waktu, kilometer lalu lintas, jumlah penumpang, konsekuensi kecelakaan kereta api, dan keluhan publik. Indeks Malmquist digunakan untuk menentukan kinerja dari masing-masing zona. KAI dapat menggunakan DEA untuk menilai kinerja berbagai zona dan untuk perbaikan pemantauan dalam konteks menjadi penyedia layanan transportasi. Zona yang tidak efisien dapat mengidentifikasi parameter untuk peningkatan antar lintas zona dan dimensi waktu. Tenaga kerja yang sangat besar untuk semua zona yang tidak efisien mengindikasikan penyebaran sumber daya, yang dapat dilihat pada tingkat kebijakan.